The Africa of 2022: Crisscrossing Crises - Siphamandla Zondi; Joseph Keutcheu; Tinuade Ojo (African Journal of Political Science, 2023)
The year 2022 marked the 20th anniversary of the African Union (AU)). The AU marked a realisation that the Organisation of African Unity (OAU) established in 1963 had fulfilled its mandate of ridding the continent of overt colonial rule and a new platform was needed to drive Africa towards full prosperity. Conceived amid the revisiting of the discourse of African Renaissance, the AU was meant to respond to both historical and contemporary imperatives. It was born to be a more agile, efficient, and effective institution. Born long after the Cold War ended, it was meant to reposition Africa strategically in global affairs.